En studie i potentiella reaktionsvägar för HCN-baserade molekyler - Bergström, Jacob; Carlsson, Jonas; Danielsson, Erika; Lennartsson, Natanael (My University, 2022)
A study in potential reaction pathways of HCN-based molecules This project delves into the reaction pathways that a HCN tetramer can follow when reacting with additional HCN molecules as well as its anion CN– . Using DFT based computational chemistry we calculate the activation energies and kinetics of several nucleophilic attacks to determine how likely they are to occur. Further analysis of an intramolecular cyclisation is performed where the effects of various side groups are studied. Among the cyclisation reactions we found one reaction containing only HCN with a very low reaction barrier.